Investigation of the Mechanical and Physical Properties of Acidic Pumice Aggregate-Reinforced Lightweight Concrete Under High-Temperature Exposure - Elyigit, Belkis; Ekinci, Cevdet Emin (Mdpi, 2025)
This study examines the mechanical and physical performance of lightweight concretes incorporating acidic pumice aggregate, with a particular focus on their behavior under thermal exposure. Pumice sourced from the Bitlis-Tatvan region was used as a partial replacement for limestone aggregate at volumetric substitution levels of 50%, 60%, and 70% (designated LC50, LC60, and LC70, respectively), alongside a conventional control mix (NC). Experimental investigations included flexural and compressive strength tests, capillary water absorption measurements, and mass loss assessments at elevated temperatures (100 degrees C, 200 degrees C, and 300 degrees C). The results indicate that increasing pumice content leads to a significant reduction in mechanical strength, as evidenced by a strong negative correlation (e.g., -0.994 for compressive strength), and results in increased water absorption due to the higher porosity of pumice. Thermal exposure caused more pronounced weight loss in pumice-rich mixtures, primarily attributable to moisture evaporation and the formation of surface voids, particularly in LC60 and LC70 specimens. Although the incorporation of pumice effectively reduces the unit weight of concrete, it compromises both strength and durability, highlighting a critical trade-off between weight reduction and structural performance. Future studies are recommended to quantitatively assess the relationship between compressive and flexural strengths to address current limitations. Additionally, advanced microstructural analyses (e.g., SEM, XRD), fire resistance evaluations at higher temperatures, and the development of hybrid mixes incorporating supplementary cementitious materials (SCMs) should be further explored.
Keywords: lightweight concrete; acidic pumice; mechanical properties; thermal behavior; water absorption; sustainability